Pendampingan Sertifikasi Halal Produk Kopi Komboro di Desa Jeporo, Kecamatan Jatipurno, Kabupaten Wonogiri: Komboro Coffee Halal Certification in Jeporo Village, Wonogiri - Budiono, Novericko Ginger; Sandy, Reza Alfreda Rahma; Arasy, Fauzan Tiko; Ath-Thifa, Balqis Naila; Salsabila, Nisrina Hasna; Rizkyana, Afini; Saragih, Nadya Azzahra Salsabilla; Silalahi, Valentino; Anjumi, Putri Dewi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
The increasing trend of halal product consumption is happening globally, including in Indonesia. Original Indonesian coffee has global market potential, considering Indonesia is the world's number 3 exporter. Coffee produced by Kopi Komboro Micro, Small, and Medium Enterprise (MSME) in Jeporo Village, Jatipurno Sub-district, Wonogiri District, Central Java Province also has the potential to be developed. This community service activity aims to provide assistance in halal certification for Kopi Komboro products in Jeporo Village, Jatipurno Sub-district, Wonogiri District, Central Java Province. The community service activities carried out are 1) Education on halal certification requirements and processes; 2) Assistance in making Taxpayer Identification Numbers (NPWP); 3) Assistance in registering Business Identification Numbers (NIB); and 4) Assistance in registering halal certification for Kopi Komboro products. The output achieved from this activity is 1) Education of MSME Kopi Komboro executives regarding the requirements and halal certification process; 2) Registration of NIB of Kopi Komboro MSME executives; 3) Registration of NPWP of Kopi Komboro MSME executives; and 4) Certification of coffee products produced by Kopi Komboro MSME executives by the Halal Product Guarantee Organizing Agency (BPJPH). Efforts to certify halal products for Kopi Komboro products are expected to increase opportunities for product market coverage and public trust regarding the halalness and quality of Kopi Komboro products.